PERAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATANBAGI PASIEN RAWAT INAP PADA RSUD dr. SOEBANDI JEMBER - Nely Supeni; Ahmad Sauqi (RELASI : JURNAL EKONOMI, 2016)
Purpose of this study is to determine the level of satisfaction of patients who had undergone hospitalization in dr. Soebandi Jember well as participants BPJS-Health as well as non BPJS health insurance participants.The data used in this study are primary data and secondary data. The samples used as many as 120 respondents. 60 respondents to respondents who had hospitalization in dr. Soebandi Jember as participants BPJS-Health and 60 for respondents who had hospitalization in dr. Soebandi Jember as non BPJS health insurance participants. The data analysis is done by non-parametric statistical tests, particularly the Chi Square test or chi-square test were symbolized by "χ2". Based on the table Chi-square test results Pearson Chi-square can be seen that significant value (p-value) = 0.001, which means smaller than α = 0.05, so the decision is to reject Ho. That is, there is a significant difference between the ministry of dr. Soebandi for inpatients participants suransi BPJS health and health insurance Non BPJS. At the patient's perception of the contingency table BPJS-health insurance membership and health suransi Non BPJS look the same percentage or proportion. Both participants and non BPJS BPJS patient perception 100.0% said easy.Based on the table Chi-square test results Pearson Chi-square can be seen significant value (p-value) = 0.088, which means greater than α = 0.05, so that the decision taken is to accept Ho. That is, there was no significant difference regarding the completion of the administration of post-hospitalization in dr Soebandi for patient participants BPJS health insurance and health insurance participants Non BPJS.